2018
DOI: 10.1007/s10886-018-0975-8
|View full text |Cite
|
Sign up to set email alerts
|

Is the Salivary Gland Associated with Honey Bee Recognition Compounds in Worker Honey Bees (Apis mellifera)?

Abstract: Cuticular hydrocarbons (CHCs) function as recognition compounds with the best evidence coming from social insects such as ants and honey bees. The major exocrine gland involved in hydrocarbon storage in ants is the post-pharyngeal gland (PPG) in the head. It is still not clearly understood where CHCs are stored in the honey bee. The aim of this study was to investigate the hydrocarbons and esters found in five major worker honey bee (Apis mellifera) exocrine glands, at three different developmental stages (new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…However, some epidermal cells that function as tegumental glands are also involved in cuticle hydrocarbon synthesis (Kramer & Wigglesworth, 1950;Abdalla et al, 2003) and such compounds can be fully or partially stored in glands after being released as secretion . The present research showed that hydrocarbons were the major compounds in CSG indicating that the studied gland may be an auxiliary source of cuticle hydrocarbons as observed in A. mellifera (Poiani & Cruz-Landim, 2017;Martin et al, 2018). In ants, the postpharyngeal gland (PPG) contains similar hydrocarbons found on cuticle surface (Bagnères & Morgan, 1991;Kaib et al, 2000).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, some epidermal cells that function as tegumental glands are also involved in cuticle hydrocarbon synthesis (Kramer & Wigglesworth, 1950;Abdalla et al, 2003) and such compounds can be fully or partially stored in glands after being released as secretion . The present research showed that hydrocarbons were the major compounds in CSG indicating that the studied gland may be an auxiliary source of cuticle hydrocarbons as observed in A. mellifera (Poiani & Cruz-Landim, 2017;Martin et al, 2018). In ants, the postpharyngeal gland (PPG) contains similar hydrocarbons found on cuticle surface (Bagnères & Morgan, 1991;Kaib et al, 2000).…”
Section: Discussionsupporting
confidence: 56%
“…Also, it aids to handle resins collected in the field (Santos et al, 2009). In A. mellifera and some Bombus species, the hydrocarbons produced by CSG are also present in the cuticle of workers (Kullenberg et al, 1973;Arnold et al, 1996;Poiani & Cruz-Landim, 2017;Martin et al, 2018). In A. mellifera, CSG may take part as an auxiliary source of cuticular hydrocarbons (Poiani & Cruz-Landim, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, it has been hypothesized that, similar to some ant species, the CHC profile of newly eclosed workers represents a ‘blank slate’ (Breed et al, 2004; Lenoir et al, 1999), and that nestmate recognition cues are subsequently acquired by individual workers primarily through the homogenization and transfer of chemicals via direct social interactions and intermediate environmental factors (Breed et al, 2015). Furthermore, it has recently been proposed that the cephalic salivary gland of honey bee workers is functionally analogous to the PPG in ants, and could be involved in the homogenization and transfer of the CHCs between colony members (Martin et al, 2018). However, when and how honey bee chemical nestmate recognition cues mature, and whether CHC homogenization mechanisms play a role in this process have not been directly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, following the development of wax glands, the HGs begin to atrophy and regress [ 4 ]. The salivary glands comprise the cephalic salivary glands (CSGs) and the thoracic salivary glands (TSGs) [ 8 ]. Each CSG is composed of two flattened pear-shaped bodies.…”
Section: Introductionmentioning
confidence: 99%